The effect of hysteroscopic endometrial polypectomy combined with LNG-IUS treatment on polyp recurrence: a multicenter retrospective study - Peng, Cheng; Liu, Jie; Ding, Hongmei; Duan, Hui; Chen, Lan; Feng, Zichang (Frontiers in Surgery, 2025)
BackgroundHysteroscopic polypectomy is a common method for treating endometrial polyps, but postoperative recurrence remains a key concern. Recently, the levonorgestrel intrauterine system (LNG-IUS) has been suggested to reduce the recurrence rate of polyps. This study aims to investigate the differences in recurrence rates and recurrence-free survival times between hysteroscopic polypectomy alone and hysteroscopic polypectomy combined with LNG-IUS, and to assess their impact on recurrence.MethodsThis study retrospectively included clinical data from 1,160 patients with endometrial polyps from 2020 to 2021, the follow-up period was 1 year. Patients were divided into two groups based on whether LNG-IUS was used after surgery: the Hysteroscopic Polypectomy group (n = 812) and the Hysteroscopic Polypectomy Combined with LNG-IUS group (n = 348). Based on the analysis, two multivariate logistic regression models were constructed: the first model included only the factors with significant differences from the statistical analysis, while the second model additionally included the treatment method. The predictive abilities of the two models for polyp recurrence were compared. The recurrence-free survival time differences between the two treatment methods were also analyzed.ResultsUnivariate logistic regression analysis showed that birth history, menstrual symptoms, quality of life, and treatment method were significantly associated with polyp recurrence. In multivariate logistic regression models, the second model, which included the treatment method, had a higher AUC (0.703) compared to the first model (AUC = 0.676), which included only significant factors. The recurrence-free survival rate in the group that received hysteroscopic polypectomy combined with LNG-IUS was significantly higher than in the hysteroscopic polypectomy group.ConclusionHysteroscopic polypectomy combined with LNG-IUS significantly reduces polyp recurrence and extends recurrence-free survival time. Multivariate logistic regression analysis indicates that including the treatment method improves the predictive ability of the model, suggesting that combined treatment plays an important role in reducing polyp recurrence and is worthy of further clinical promotion and application.